IMPLEMENTASI SUPERVISI KLINIS DALAM MENETAPKAN TUJUAN PEMBELAJARAN DI SMP NEGERI 2 PEMALANG - Urip Suwarniti; Soedjono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study to describe the implementation of Clinical Supervision in helping teachers set learning objectives that are in accordance with student characteristics and learning outcomes at SMP Negeri 2 Pemalang. Clinical Supervision is a collaborative mentoring approach for teachers in teacher professional development. Clinical Supervision carried out on teachers at SMP Negeri 2 Pemalang aims to determine learning objectives with stages of planning, implementation, evaluation and follow-up. The research method used is descriptive qualitative with data collection techniques through interviews, observations, and documentation studies. The results of the study indicate that the implementation of clinical supervision can improve teachers' ability to formulate learning objectives that are in line with learning outcomes and student characteristics.